2022
DOI: 10.1371/journal.pntd.0010889
|View full text |Cite
|
Sign up to set email alerts
|

The number of cases, mortality and treatments of viral hemorrhagic fevers: A systematic review

Abstract: Background Viral hemorrhagic fevers (VHFs) are a group of diseases, which can be endemo-epidemic in some areas of the world. Most of them are characterized by outbreaks, which, occur irregularly and are hard to predict. Innovative medical countermeasures are to be evaluated but due to the field specificities of emerging VHF, challenges arise when implementing clinical studies. To assess the state of the art around VHFs, we conducted a systematic review for all reports and clinical studies that included specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…This could be due to differences in both the resilience of healthcare systems, patient demographics and conflict (13,42,43). The range in our estimates are consistent with these previous reviews (18,(24)(25)(26)(27). However, there is insufficient evidence to distinguish whether one or more species have an inherently higher severity, or whether the observed differences are driven by contextual factors such as improved case management over time.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This could be due to differences in both the resilience of healthcare systems, patient demographics and conflict (13,42,43). The range in our estimates are consistent with these previous reviews (18,(24)(25)(26)(27). However, there is insufficient evidence to distinguish whether one or more species have an inherently higher severity, or whether the observed differences are driven by contextual factors such as improved case management over time.…”
Section: Discussionsupporting
confidence: 76%
“…Disagreements were resolved by consensus between reviewers. We used backward citajon chaining from 12 of the 179 review papers (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) identified during screen to add in missing papers (see SM Section 2.3).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…It is possible that a correlation exists between the extent of UN 5 continuity and viral pathogenicity. In fact, only ZEBOV and MARV have ever recorded an approximately 90% case fatality rate among viruses in the family Filoviridae (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Between 1998 and 2000, an outbreak occurred in the Democratic Republic of Congo, resulting in > 120 deaths with an associated case fatality rate of 83%. What was regarded as the largest MARV outbreak in history occurred in Angola between 2004 and 2005 with 374 cases, resulting in a fatality rate of almost 90% [6] . In 2008, however, 2 cases of MVD were imported outside Africa and were reported among tourists who had visited caves inhabited by bat colonies in Uganda.…”
Section: Historical Accountsmentioning
confidence: 99%